BEYOND MORTALITY: EVALUATING INSECTICIDE IMPACT ON Spodoptera exigua FEEDING AND DAMAGE - Handoko, Bayu; Febrayanto, Catur Raharjo; Susiyanti, Fitri; Mulyana, Ibnu Hendra (Institute of Computer Science (IOCS), 2024)
The study addresses the pressing issue of effective pest control in agriculture, focusing on the impact of pesticides on Spodoptera exigua, a notorious pest of agricultural crops. The research aims to investigate the influence of different insecticide active ingredients and concentrations on mortality, feeding inhibition, and damage levels to develop optimal control strategies. The observed variables were mortality, feeding inhibition, and damage level. The study utilized regression and correlation analysis to determine the influence of harvested area on shallot production and relationship between harvested area and shallot production, generalized linear model (GLM) analysis to evaluate the effects of insecticide treatments and employed Duncan's multiple range test (DMRT) to identify the most effective factors. Results indicate that chlorpyrifos emerged as the most potent insecticide in terms of mortality, while chlorantraniliprole + indoxacarb and chlorpyrifos showed high feeding inhibition. Chlorpyrifos, particularly at the recommended concentration, minimized damage levels to the host plant. These findings underscore the importance of considering multiple factors when implementing pest control measures for sustainable agricultural practices.